Entrepreneurial cognition and internationalization speed: towards a potential moderating effect of experiential and rational information processing - Vlačić, Božidar (2022)
This study explores the influence that entrepreneurial cognition, in terms of the dichotomy in human information processing, has on the earliness of internationalization and post-entry speed. Entrepreneurial cognition is investigated through the lens of the dual-process theory, which posits that human information processing is formed of two systems, the experiential cognitive system (System 1) and the rational and analytical cognitive system (System 2). The speed of the entire internationalization process is analyzed in terms of earliness (how soon after inception a company enters its first international market) and post-entry speed (how fast it enters new markets after the first internationalization). Drawing on ten cases, we find that companies that internationalized earlier and faster were managed by entrepreneurs with higher levels of the experiential cognitive system. In contrast, companies that internationalized later and more gradually were managed by entrepreneurs with higher levels of the rational cognitive system. Thus, our study reveals that the speed of the entire process of internationalization is governed, at least partially, by the entrepreneur’s cognition. On the basis of our findings, we introduce three propositions on the moderation that the entrepreneur’s cognition exerts on the well-established relations between environmental signals and both earliness of internationalization and post-internationalization speed.